Application of Data Mining in Determining the Performance of Family Planning Field Officers Using the C4.5 Algorithm - Sulaiman, Oris Krianto; Siambaton, Muhammad Zulfan Syuri (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2025)
The performance of Family Planning Field Officers plays a crucial role in the success of family planning programs. Accurate and objective performance evaluation is essential to support effective decision-making and policy formulation. This study applies data mining techniques to determine the performance of Family Planning Field Officers using the C4.5 decision tree algorithm. The dataset used in this research consists of officer performance indicators, including service coverage, counseling activities, reporting accuracy, and community participation. The C4.5 algorithm is employed to classify officer performance into predefined categories based on these attributes. The resulting decision tree provides interpretable classification rules that can support managerial decision-making. Experimental results show that the proposed model achieves satisfactory classification accuracy and demonstrates the effectiveness of the C4.5 algorithm in extracting meaningful patterns from performance data. This study highlights the potential of data mining approaches to enhance performance evaluation systems in public service institutions, particularly in the field of family planning management.